Efficiency of different adhesive for making laminated bamboo panels - Kravchenko, Grégory Adad; Evaldo de Melo; Pasqualetto, Antonio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This work has as main goal to evaluate the efficiency of different adhesives used for making laminated bamboo panels. This technical-scientific research laboratory tests were performed, where properties of twelve laminated bamboo beams can be compared. The plant was chosen type Dendrocalamus giganteus. This genus is one of the best to perform carpentry work. For each type of adhesive applied to the plates of laminated bamboo, bending tests (reduced size), hardness, density, screw withdrawal, shear stress and shear stress at the glue line, a tool constituted conclusive on the workability of the different Products promoters junction between the parts that form the plywood. In some types of adherent reviews have not responded well to tests, bringing the disruption of certain body-of-evidence, but one can prove the efficiency of adhesives used in the manufacture of laminated bamboo. This work is the result of a detailed study on the plates made with bamboo. In environments with significant levels of humidity and temperatures can shorten the use of furniture, laminate made with Dendrocalamus giganteus has higher efficiency over other matters falling in the furniture industry.